2022
DOI: 10.3390/jcm11175075
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of AFP, AFP-L3, or PIVKA-II for Hepatitis C Virus-Associated Hepatocellular Carcinoma: A Multicenter Analysis

Abstract: Background and Aim: Alpha-fetoprotein (AFP), a lens culinaris agglutinin-reactive fraction of AFP (AFP-L3), is a protein that is induced by vitamin K deficiency or antagonist-II (PIVKA-II) that has been clinically used as a serum biomarker for early detection and diagnosis of hepatocellular carcinoma (HCC). Diagnostic performance of each serum biomarker alone, or their combinations for the detection of hepatitis C virus (HCV)-associated HCC were compared. Methods: Serum AFP, AFP-L3, and PIVKA-II levels were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…Studies suggest that AFP and PIVKA-II are complementary biomarkers as their production occurs through different pathways. [15][16][17][18] In patients with very early/early HCC the diagnostic accuracy of each biomarker was almost equal (AUROC 65.8% for AFP and 65% for PIVKA-II) and did not improve with the combination of them (AUROC 64.2%) whereas there was an additive, complementary effect of PIVKA-II to AFP in the HCC diagnosis in intermediate and advanced stages, according to the results of our study. It seems that the combination of the two biomarkers is not the most useful tool available to predict the presence of very early or early HCC in advanced cirrhotic patients, irrespective of the imaging results.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Studies suggest that AFP and PIVKA-II are complementary biomarkers as their production occurs through different pathways. [15][16][17][18] In patients with very early/early HCC the diagnostic accuracy of each biomarker was almost equal (AUROC 65.8% for AFP and 65% for PIVKA-II) and did not improve with the combination of them (AUROC 64.2%) whereas there was an additive, complementary effect of PIVKA-II to AFP in the HCC diagnosis in intermediate and advanced stages, according to the results of our study. It seems that the combination of the two biomarkers is not the most useful tool available to predict the presence of very early or early HCC in advanced cirrhotic patients, irrespective of the imaging results.…”
Section: Discussionsupporting
confidence: 72%
“…PIVKA‐II revealed the best predictive performance compared to AFP and AFP‐L3, in studies which evaluated HCC patients and patients with chronic hepatitis C 15 or patients with benign liver lesions, liver metastases, and other gastrointestinal malignancies 16 . It is important to note, that in these studies the control group was either non‐cirrhotic patients 16 or mainly patients with compensated Child‐Pugh A cirrhosis as presented in the study by Liu S et al., 15 in contrast to our study in which approximately half of the study population exhibited advanced decompensated liver cirrhosis. Non‐cirrhotic control groups may overestimate the diagnostic accuracy of each individual biomarker as well as the combination of them in the detection of HCC, as it has been observed that liver cirrhosis significantly impacts serum PIVKA‐II and AFP levels 13,14 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations